1999
DOI: 10.1159/000010112
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Compromise Assessed byDoppler Ultraso und of Venous Flow in Pregnancy-Induced Hypertension

Abstract: The purpose of this study was to determine the change of venous flow patterns in the inferior vena cava of fetuses in pregnancy-induced hypertension (PIH). We studied 80 normal pregnant women and 46 pregnant women with PIH and their fetuses. We determined the pulsatility index (PI) for arterial vessels, the ratio of peak flow velocities in early diastole and late diastole (E/A) in atrioventricular valves, and the preload index for the inferior vena cava. Twelve of the 46 PIH women showed an umbilical artery PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, Ochi et al [19] showed an increment in the ratios in early and severely affected IUGR fetuses. In a longitudinal study, Figueras et al [20] followed 22 IUGR fetuses and reported significantly lower E/A ratios in both AV valves compared to normally grown fetuses with early deterioration of the right E/A ratios.…”
Section: Clinical Implications Of the E/a Ratios And Outflow Tractsmentioning
confidence: 99%
“…However, Ochi et al [19] showed an increment in the ratios in early and severely affected IUGR fetuses. In a longitudinal study, Figueras et al [20] followed 22 IUGR fetuses and reported significantly lower E/A ratios in both AV valves compared to normally grown fetuses with early deterioration of the right E/A ratios.…”
Section: Clinical Implications Of the E/a Ratios And Outflow Tractsmentioning
confidence: 99%